Aplicación de las metodologías 8D y AMFE para reducir fallos en una fábrica de refrigeradoras - Izaguirre Neira, Javier Gabino (2017)
In a manufacturing company of white goods, it has identified a specific line of refrigerators that has a high percentage of failures at end users compared with the other lines of the same factory. By analyzing the information coming from the technical services and supported on quality tools the main problems are identified, causes are searched, improvements are proposed and subsequent failures are forewarned. Various actions will result to the reduction of market problems, it will help to reduce warranty costs for each product and especially these will impact very favorable for brand image.